RISKS OF UKRAINIAN BUSINESS ENTERING THE EUROPEAN MARKET - Атаманчук, Зорина; Ковальчук, Анастасія (SWorldJournal, 2024)
The article is devoted to the risks associated with the Ukrainian foreign economic activity entities entering into the markets of European countries, particularly the European Union countries, studing. It is substantiated that entering the European marke